Pengaruh E-service Quality, E-trust Dan E-wom Terhadap Keputusan Pembelian Pada Onlineshop (Studi Pada Pengguna Onlineshop di Kota Malang) - Ifah, Nadrian; Djaelani, Abdul Kodir; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This exploration means to decide the impact of E-service quality, E-trust and E-wom on purchasing decisions in onlineshops. (investigation of onlineshop clients in Malang City) This examination technique utilizes quantitative strategies. The populace involved was online shop clients in the city of Malang and gotten 70 respondents utilizing purposive testing methods with rules set by the analyst. The information assortment strategy is by utilizing on the web and disconnected surveys. The information examination procedure utilized is different straight relapse investigation with the IBM SPSS Statictic 26 program. The consequences of this exploration show that E-service quality, E-trust and E-wom at the same time impact purchasing decisions. To some degree, E-service quality has no impact on purchasing decisions, E-trust to some extent impacts purchasing decisions. E-wom to some degree impacts purchasing decisions. Keywords: Purchasing Decisions, E-service Quality, E-trust, E-wom